We don't do dots : Aboriginal art and culture in Wilcannia, New South Wales - Gibson, Lorraine (Sean Kingston Publishing, 2013)
What does it mean when whites say that certain Australian Aboriginal people have 'no culture' but accept that they have art? Why are notions and images of Aboriginal art and culture still dominated by those from the centre and north of the Australian continent, even though most Aborigines reside in the south-east? This book explores these questions, why they matter, and to whom they matter. It draws on extensive fieldwork with Barkindji Aboriginal people in the small country town of Wilcannia, New South Wales. The richly textured ethnographic analysis examines how notions of Aboriginal art and.